The Potential of Natural Ingredients Ziziphus spina-christi, Nauclea subdita, and Sauropus androgynus as Skin Care - Alliza Nur Shadrina; Nieda Berliana Eiko; Wella Sulvita; Nia Yuniarsih (Archives of The Medicine and Case Reports, 2022)
Skin aging is characterized by wrinkling, dryness of the skin, discoloration, and loss of elasticity. In addition to genetic factors, environmental hazards such as UV radiation and oxidative stress contribute to skin aging. There is evidence to support that antioxidants can reduce the damage done by oxidative stress in the skin. However, criticism has been raised on the safety of synthetic antioxidants, so efforts have been made to explore various natural substances as powerful antioxidants. Currently, many plant extracts are used in cosmetics for the optimization of antioxidant effects. Bidara leaves (Ziziphus spina-christi l.), Bangkal trunk bark (Nauclea subdita (korth). steud.) and katuk leaves (Sauropus androgynus (l.) have the potential to be developed as skin care.